If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 21 = -2x + 9 Reorder the terms: 21 + x = -2x + 9 Reorder the terms: 21 + x = 9 + -2x Solving 21 + x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 21 + x + 2x = 9 + -2x + 2x Combine like terms: x + 2x = 3x 21 + 3x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 21 + 3x = 9 + 0 21 + 3x = 9 Add '-21' to each side of the equation. 21 + -21 + 3x = 9 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 9 + -21 3x = 9 + -21 Combine like terms: 9 + -21 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 3x-127=4x+13-11x | | 192-(40*x+2*x^2)=0 | | 9x-22=7x-2 | | 8y-5=-5 | | 245n^2+70n-240=0 | | X+142=3x+64 | | x*2+102=x*8-6 | | 4x/3= | | 22-5x=6-7x | | 5-3(2-3x)=5 | | 3x-12=-23-2x | | 9+9x=-7+x | | 46-2b=10 | | 9+9a=-7xa | | 5x^2+1x-15=0 | | 4(y-11)=11(y-4) | | x^3+2x+7=0 | | 3(2t+5)=4(5t+7) | | 10p^2-19p-15=0 | | 4x-2=7x-10 | | 9k-6-3(2-5k)= | | 3x^2+7x-41=0 | | 14.95+.13x=-15+.39 | | 6x+67=12x-5 | | k^2-k-56=0 | | 75/(-5)(-3)/.50(6) | | 14.95-.13x=-15+.39 | | 2e-x=1 | | 5+12x=16+x | | 2(5+x)-12=4 | | n^2-n-2=0 | | 5x-x=-10.4-2 |